Validity and reliability of the Adapted Katz Index Scale (Research, Society and Development, 2020)
This study aimed to assess whether the "Adapted Katz Scale Index" device can be effective and understood by the elderly population and thus verify its validity and reliability. To answer this first stage, 29 participants were selected, all with ages equal to or over 60 years old, participants of an event aimed at the elderly population and submitted to 1 questionnaire and 3 evaluations: Sociodemographic Questionnaire, Mental State Mini Exam, Katz Index Scale and Adapted Katz Index Scale. This study is a cutout of the institutional survey "Evaluation of daily life activities in elderly with or without cognitive alteration". The survey showed that 29 [100%] of the participants obtained the same score and classification when evaluated by the instrument Katz Index Scale and Adapted Katz Index Scale, which demonstrates its validity and reliability. As for its applicability 93.1% of those surveyed consider the instrument Adapted Katz Index as a facilitator. The instrument presents potential to become a new health evaluation instrument, for that, it becomes relevant the development of subsequent studies and the continuity of the research, carrying out other necessary procedures such as verification of sensitivity and responsiveness, besides the judgment of specialists in the health area and the finalization with the aphasic population.